Prevalence and factors associated with mercury exposure in riverside communities in the Brazilian Western Amazon - Vanessa Alves Mendes; Débora Aparecida da Silva Santos; Edson dos Santos Farias; Dario Pires de Carvalho; Wanderley Rodrigues Bastos
ABSTRACT Objective: to verify mercury exposure prevalence and identify its possible associated factors in two riverside communities in the Madeira River basin of the Western Brazilian Amazon. Method: a cross-sectional study comprising 95 children and adolescents. Age cycle, school attendance, Bolsa Família, number of siblings, meals, fish consumption, height by age were measured. Binary logistic regression was used to verify relationships between mercury exposure and its possible associated factors. Results: the general prevalence of mercury exposure was 46.3%; children, 35.4%; and adolescents, 57.4%. Associated factors were fish consumption (aOR=1.84; 95%CI 1.56-2.16), age cycle (aOR=2.50; 95%CI 1.09-5.7), parasites (aOR=1.22; 95%CI 1.02-2.71), and short stature (aOR=1.32; 95%CI 1.05-2.02). Conclusion: mercury exposure prevalence in riverside children and adolescents was considered worrying, with association with fish consumption, adolescence, parasites, and short stature.